2020
DOI: 10.1155/2020/8396708
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota and Oxidative Stress in Autism Spectrum Disorders (ASD)

Abstract: Autism spectrum disorders (ASDs) are a kind of neurodevelopmental disorder with rapidly increasing morbidity. In recent years, many studies have proposed a possible link between ASD and multiple environmental as well as genetic risk factors; nevertheless, recent studies have still failed to identify the specific pathogenesis. An analysis of the literature showed that oxidative stress and redox imbalance caused by high levels of reactive oxygen species (ROS) are thought to be integral parts of ASD pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 107 publications
(104 reference statements)
0
34
0
Order By: Relevance
“…The taurine and hypotaurine metabolism pathway also differed significantly between the two groups. Oxidative stress imbalance is considered to be important components of the pathophysiology of ASD, and antioxidant therapy may improve the prognosis of ASD ( 45 , 46 ). Park et al reported that taurine, as an antioxidant and regulator of inflammation, might be a valid biomarker for ASD ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The taurine and hypotaurine metabolism pathway also differed significantly between the two groups. Oxidative stress imbalance is considered to be important components of the pathophysiology of ASD, and antioxidant therapy may improve the prognosis of ASD ( 45 , 46 ). Park et al reported that taurine, as an antioxidant and regulator of inflammation, might be a valid biomarker for ASD ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is not only due to their impact on the microglia and the BBB permeability, but also to the production of SCFAs. As mitochondrial fuels, they may contribute to the uncontrolled production of ROS/RONS, particularly when the mitochondrial function is already altered [ 157 ] and the synthesis of SCFAs is increased due to alterations in the microbial composition. In fact, some bacterial species are more active in the production of SCFAs, such as Bacteroides spp.…”
Section: Microbiota–gut–brain Axis and Attention-deficit And/or Hymentioning
confidence: 99%
“…the evidence for markers of oxidative stress associated with glutathione metabolism, lipid peroxidation, protein oxidation, DNA oxidation and antioxidant enzyme activity has been comprehensively reviewed in recent years [45,[98][99][100][101][102][103]. In the context of neurodevelopment, this has significant implications for the redox regulation of neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Given that mitochondrial dysfunction is an established component of ASD aetiology, and that metabolic state plays a central role in neuronal differentiation, our review highlights a potentially important connection between mTORC1, oxidative phosphorylation and neuropathology in ASD. Finally, our review integrates all of the above with the thoroughly reviewed evidence for neuroinflammation and oxidative stress in ASD [49][50][51][52][98][99][100][101][102][103] by considering the role of mitochondrial metabolism in gliosis and microglial activation, and the downstream consequences for synaptogenesis, neuronal connectivity and behavioural phenotypes.…”
Section: Discussionmentioning
confidence: 99%